Pemurnian Produk Mono-Diasilgliserol (MDAG) Hasil Gliserolisis Kimia dengan Metode Demulsifikasi Krim - Satiti Kawuri Putri; Purwiyatno Hariyadi; Mursalin Mursalin; Nuri Andarwulan (agriTECH, 2020)
Cream demulsification is one of the purification method for separating the glycerol residue contained as emulsion with MDAG’s product. This method could be used to break emulsion system by adding electrolyte solution. This research aims to compare the performance of calcium chloride and calcium nitrate as electrolyte solution that is used in the process of cream demulsification. MDAG used was Fully Hydrogenated Palm Kernel Oil (FHPKO) from glycerolysis process. Based on student t-test, there was no significant difference (p>0,05) detected between the products of cream demulsification method using calcium nitrate and calcium chloride as electrolyte solution. It was discovered that calcium nitrate reduced residual glycerol from 11,69±0.88% to 0,57±0,07%; with characteristics of MDAG’s products were free fatty acid (ALB) of 8,51±0,94%, monoacylglycerol (MAG) of 31,53±3,27%, diacylglycerol (DAG) of 19,46±0,52%, triacylglycerol (TAG) of 39,93±4,66% and yield of 81,00±3,61%.respectively. In other hand, calcium chloride reduced residual glycerol from 11,69±0,88% to 0,64±0,06%; with characteristics of MDAG’s products were ALB of 8,91±0,71%, MAG of 9,79±1,97%, DAG of 19,16±0,53%, TAG of 41,49±3,24% and yield of 80,00±4,00%, respectively. Therefore, calcium nitrate can be to replace calcium chloride as electrolyte solution in cream demulsification method, especially in reducing the glycerol residue.